LncRNA GAS5 represses stemness and malignancy of gliomas via elevating the SPACA6-miR-125a/let-7e Axis - Wu, Shuang; Ren, Kaixi; Zhao, Jing; Li, Juan; Jia, Bo; Wu, Xiuquan; Dou, Yanan; Fei, Xiaowei; Huan, Yu; He, Xin; Wang, Tingting; Lv, Weihao; et al. (Frontiers in Oncology, 2022)
Glioblastoma (GBM) is a highly invasive neurological malignancy with poor prognosis. LncRNA-GAS5 (growth arrest-specific transcript 5) is a tumor suppressor involved in multiple cancers. In this study, we explored the clinical significance, biological function, and underlying mechanisms of GAS5 in GBM. We showed that lncRNA-GAS5 expression decreased in high-grade glioma tissues and cells, which might be associated with poor prognosis. GAS5 overexpression lowered cell viability, suppressed GBM cell migration and invasion, and impaired the stemness and proliferation of glioma stem cells (GSCs). We further discovered that GAS5 inhibited the viability of glioma cells through miR-let-7e and miR-125a by protecting SPACA6 from degradation. Moreover, GAS5 played an anti-oncogenic role in GBM through the combined involvement of let-7e and miR-125a in vivo and in vitro. Notably, these two miRNAs block the IL-6/STAT3 pathway in tumor tissues extracted from a xenograft model. Taken together, our study provides evidence for an important role of GAS5 in GBM by affecting the proliferation and migration of GSCs, thus providing a new potential prognostic biomarker and treatment strategy for GBM.